Differential perceptions of quality of life (QoL) in community-dwelling persons with mild-to-moderate dementia. (August 2014) - Tay, Laura; Chua, Kia Chong; Chan, Mark; Lim, Wee Shiong; Ang, Yue Ying; Koh, Evonne; Chong, Mei Sian
ABSTRACT Background: Discordance between patient- and caregiver-reported quality of life (QoL) is well recognized. This study sought to (i) identify predictors of discrepancy between patient- and caregiver-rated QoL amongst community-dwelling persons with mild-to-moderate dementia, and (ii) differentiate between patients who systematically rate their QoL lower versus those who rate their QoL higher relative to their caregiver ratings. Methods: We recruited 165 patient–caregiver dyads with mild-to-moderate dementia. Quality of life in Alzheimer's disease (QoL-AD) scale was administered separately to patients and caregivers. Data on socio-demographics, interpersonal relationship, and disease-related characteristics (cognitive performance, mood, neuropsychiatric symptoms, functional ability, and caregiver burden) were collected. Patient–caregiver dyads were categorized based on whether patient-rated QoL was lower or higher than their respective caregiver ratings. Univariate analyses and multiple regression models were performed to identify predictors of dyadic rating discrepancy. Results: Mean patient-rated QoL was significantly higher than caregiver rating (mean difference: 3.8 ± 7.1, p < 0.001). Majority (111 (67.2%)) of patients had more positive self-perceived QoL (QoL-ADp (QoL-AD self rated by the patient) > QoL-ADc (QoL-AD proxy-rated by a caregiver)), compared with those (44 (26.7%)) with poorer self-perceived QoL (QoL-ADp < QoL-ADc). Patient's education level, depressive symptoms, and severity of neuropsychiatric symptoms predicted magnitude of discrepancy. Depression (OR = 1.17, 95% CI = 1.02–1.35) and being cared for by other relative (non-spouse/adult child; OR = 7.54, 95% CI = 1.07–53.03) predicted poorer self-perceived QoL. Conclusions: Dyadic rating discrepancy in QoL should draw the clinician's attention to patient depression and neuropsychiatric symptoms. Consideration should also be given to nature of patient–caregiver relationship when discordance between patient and caregiver assessments of QoL is observed.